Laser shearography investigation on common engineering materials - Neo, Jin Seng (Nanyang Technological University, 2020)
This project aims to investigate the capability of laser shearography as a non-destructive testing tool for evaluation of common engineering materials like steel, aluminium, copper and carbon fiber through mechanical and thermal loading schemes. Engineering materials have distinct chemical and physical properties. The conventional NDT techniques like ultrasound, magnetic particle testing and liquid penetration can be used to evaluate for defects, however, they suffer from long test times. In aerospace and defense industries, the components need to be tested very fast. Thus, in order to evaluate the components at a rapid rate, optical technique like laser shearography is the sought after method. This project in this context, aims to explore the use of a commercial laser shearography system to understand the role of shape and material of several metallic and non-metallic components upon two loading schemes, mechanical and thermal. Firstly, the system is setup for evaluating a standard aluminium test sample. The role of its shape is understood by analysing the interference fringe pattern obtained upon mechanical and thermal loading. Next, the similar process is carried on carbon fiber materials (raw and cured). Laser shearography, which is one of the optical non-destructive testing (NDT) methods, is used to identify defects in engineering components. It uses a coherent laser light to generate speckle patterns for determining the first derivative of displacement, based on which the defects on the subsurface can be detected and evaluated. To detect these defects (like micro-cracks and sub-surface defects), minute strains or deformations have to be induced in the materials. There are various methods to induce these deformations, examples include thermal, mechanical and vacuum loadings. A Charge-Coupled Device (CCD) cameras integrated into the laser shearograpic system, can capture the speckle patterns and, or speckle interference fringes using speckle interferometry principle. The information on the surface or sub-surface defects in the material can be obtained by the interference fringes captured which is then processed by the image processing software to yield defect positions and the amount of deformation. As part of studying the role of component shape, steel, copper and aluminium plates of square and rectangular shapes are procured. The jigs for loading the samples are designed using computer aided design (CAD) software, and fabricated. The jigs and samples are then used in the actual experiment to carry out the mechanical and thermal loading schemes. The experiments are conducted multiple times to ensure consistent and fair results. The results of mechanical and thermal loading indicate the various defect points and nature of deformations in the materials on which experiments are performed. Symmetric double bull’s eye or butterfly fringe patterns are obtained, with smooth displacement curves, for perfect square sample with no defects. For defect-free rectangular samples, straight-line fringes are obtained. This is attributed to the non-uniform bending of the sample upon mechanical loading. The deformation and defect profiles upon thermal loading of carbon fiber and aluminium are presented and discussed next. In short, the obtained results show the shape and material property dependency of steel, aluminium, copper and carbon fiber materials, which are used widely in major construction and aerospace industries. The results provide a platform to put-forth the use of optical laser shearography technique for rapid whole field inspection of these materials. We envisage that the results motivate further research into using the technique for composite materials and alloys to decipher the role of material anisotropies and multi-material interactions in a component.